Study on Processing Technology and Quality of Moringa oleifera leaves with y - Aminobutyric Acid - Wei Zhou; Qian Li; Changqing Guo; Yupo Cao; Shaodan Peng; Wei Jing; Jihua Li (MATEC Web of Conferences, 2017)
In order to obtain the high level of γ-aminobutyric acid Moringa oleifera leaves, Use 7% sodium glutamate solution to soak the fresh Moringa oleifera leaves, study effect of different treatment times and three different drying methods( hot air drying, vacuum freeze drying, shadow drying) on the formation of y-aminobutyric acid and quality (total flavonoids, soluble sugar, amino acids, polyphenols, color)of dried Moringa oleifera leaves. The results indicated that shadow-dried Moringa oleifera leaves had the hightest retention of γ-aminobutyric acid, but its browning degree were not preferable, soluble sugar was damaged gravely, and its vulnerable to weather conditions. Vacuum freeze dried Moringa oleifera leaves had the hightest retention of flavonoids, polyphenols and amino acids. The y-aminobutyric acid content of Vacuum freeze dried and hot air dried Moringa oleifera leaves had no much difference. Hot air dried Moringa oleifera leaves browning degree were preferable, it’s had an moderate content of soluble sugar and amino acids, the short drying time is characteristics of this drying method.with the treatment time increased, the content of γ-aminobutyric acid and amino acids content first increased and then decreased. Flavonoids and polyphenols content first decreased and then increased. Soluble sugar content decreased. In summary, after soaking with 7% sodium glutamate solution for 10h, then dried by hot air drying(drying temperature of 60°C), was the most suitable way for industrial production of the high level of γ-aminobutyric acid Moringa oleifera leaves.